2023
DOI: 10.1097/ico.0000000000003158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Thickness Measurements After Customized Corneal Crosslinking Using High-Resolution Optical Coherence Tomography and Scheimpflug Tomography

Abstract: Purpose:The aim of this study was to compare the evolution of corneal pachymetry after customized corneal crosslinking (CXL) between Scheimpflug-based and optical coherence–based corneal tomography (OCT).Methods:In this retrospective study, central corneal thickness (CCT), thinnest corneal thickness, and epithelial thickness of 33 eyes of 33 patients with keratoconus were measured preoperatively and 1, 3, and 12 months after customized CXL using the Pentacam HR and the MS-39. The mean pachymetry values of meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The researchers utilized the Pentacam HR and the MS-39 AS-OCT imaging techniques to evaluate the corneal thickness measurements preoperatively and 1, 3, and 12 months. Their findings indicated that the Pentacam HR method exhibited a tendency to underestimate pachymetry measurements in cases when corneal haze was present (19). Furthermore, Ashour et al found that the Pentacam HR (Oculizer II) had a tendency to underestimate corneal thickness readings in keratoconus (KC) and scarred corneas when compared to AS-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers utilized the Pentacam HR and the MS-39 AS-OCT imaging techniques to evaluate the corneal thickness measurements preoperatively and 1, 3, and 12 months. Their findings indicated that the Pentacam HR method exhibited a tendency to underestimate pachymetry measurements in cases when corneal haze was present (19). Furthermore, Ashour et al found that the Pentacam HR (Oculizer II) had a tendency to underestimate corneal thickness readings in keratoconus (KC) and scarred corneas when compared to AS-OCT.…”
Section: Discussionmentioning
confidence: 99%